Taxonomical notes on the genus Anthaxia Eschscholtz, 1829 (Coleoptera: Buprestidae) from Malaysia and Indonesia and a new record for Brunei - Plachetka, Mikuláš; Rydzi, Daniel (Zootaxa, 2026)
Two new species and one subspecies of the genus Anthaxia (Haplanthaxia) Reitter, 1911 are described, compared with the most similar species and illustrated here: Anthaxia (Haplanthaxia) erjani sp. nov. from Indonesia, Anthaxia (Haplanthaxia) serramera sp. nov. from Malaysia and Anthaxia (Haplanthaxia) javanica continentalis ssp. nov. from Malaysia, all belonging to the Anthaxia (Haplanthaxia) aeneocuprea species-group. Anthaxia (Merocratus) priska Bílý, 2019 is synonymized with Anthaxia (Haplanthaxia) dayaka Bílý, 1991. A lectotype is designated for Anthaxia (Haplanthaxia) javanica Obenberger, 1924 and new distributional records for this species are given.